O modelo antitruste brasileiro (Lei nº 12.529/2011) - Neves, Luiz das (2015)
This thesis aims to present the Brazilian Competition Law, from international sources of its formation and dynamism to the rules insertion in Brazil and current legislation, Law No. 12.529 / 11. From literature searches containing doctrines, history and law, as well as research in newspapers and websites, the work began by the elements that gave rise to antitrust formatting, a brief historical overview, theoretical and multidisciplinary of the Institute, to finally reach the legal classic figures of the current antitrust analysis. Following the study of the modeling of the Brazilian antitrust system, its historical, constitutional issues and better adaptation from the constitutional will of 1988, by the market economy in which the Law No. 12.529/11 did well to reassure a antitrust defense and to restructure the Brazilian System of Competition Defense. At last, by using the menus of trials from CADE and newspaper articles, as well as verification of public databases, we tried to extract conclusions on the good technique of the national antitrust and its adaptation to the Brazilian reality